Endometrium development patterns and BMI groups among in vitro fertilization patients; prognostic aspects - Vedelek, Viktor; Bicskei, Petra; Tábi, Mariann; Lajkó, Noémi; Ékes, Csaba; Bereczki, Kristóf; Meixner-Csáti, Zsófia; Sinka, Rita; Vágvölgyi, Anna; Zádori, János (Frontiers in Endocrinology, 2024)
The impact of the obesity pandemic on female reproductive capability is a factor that needs to be investigated. In addition, the link between endometrial thickness and in vitro fertilization (IVF) outcomes is contentious. Goal: Our goal was to analyze the association among endometrium development, hormone levels, embryo quality, clinical pregnancy, anamnestic parameters, and body mass index (BMI) in women receiving IVF treatment. Patients and methods: 537 participants undergoing IVF/ICSI cycles with successful oocyte retrieval were enrolled. Subjects were divided into four BMI based groups: underweight (UW; n=32), normal weight (NW; n=324), overweight (OW; n= 115), obesity (OB; n=66).Anthropometric and anamnestic parameters, characteristics of stimulation, endometrial thickness on the day of hCG injection, at puncture, at embryo transfer, FSH, LH, AMH, partner's age and the semen analysis indicators, embryo quality, clinical pregnancy, were recorded and analyzed. Support Vector Machine (SVM) was built to predict potential pregnancies based on medical data using 22 dimensions.In accordance with BMI categories, when examining pregnant/non-pregnant division, the average age of pregnant women was significantly lower in the UW (30.9±4.48 vs. 35.3±5.49 years, p=0.022), NW (34.2±4.25 vs. 36.3±4.84 years, p<0.001), and OW (33.8±4.89 vs. 36.3±5.31 years, p=0.009) groups. Considering FSH, LH, and AMH levels in each BMI category, a statistically significant difference was observed only in the NW category FSH was significantly lower (7.8±2.99 vs. 8.6±3.50 IU/L, p=0.032) and AMH (2.87±2.40 vs. 2.28±2.01 pmol/L, p=0.021) was higher in pregnant women. There were no further statistically significant differences observed between the pregnant and non-pregnant groups across any BMI categories, especially concerning endometrial development. Surprisingly, BMI and weight correlated negatively with p<0.001; p<0.001, p<0.001; p<0.001) in the whole population. SVM model average accuracy on predictions was 61.71%.Discussion: A convincing correlation between endometrial thickness development and patients' BMI could not be substantiated. However, FSH and LH levels exhibited a surprising decreasing trend with increasing BMI, supporting the evolutionary selective role of nutritional status. Our SVM model outperforms previous models; however, to confidently predict the outcome of embryo transfer, further optimization is necessary.